The Influence of Unemployment, Human Development Index and Inflation on Economic Growth in Bengkulu Province - Novita Wulandari; Ellya Revolina; Fitriani Ariska (Jurnal Ekonomi Balance, 2025)
This study investigates the impact of the open unemployment rate (TPT), Human Development Index (HDI), and inflation on economic growth in Bengkulu Province over the 2014–2023 period. Employing a quantitative approach, the research utilizes secondary data sourced from the Central Bureau of Statistics. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The findings reveal that, on a partial basis, only the HDI has a statistically significant influence on economic growth, while the open unemployment rate and inflation do not demonstrate significant effects. However, when analyzed simultaneously, all three variables collectively exert a significant impact on economic growth in the province. These results underscore the pivotal role of human capital development in driving sustainable economic performance. Enhancing education, healthcare, and general welfare as reflected in HDI can contribute more effectively to long-term economic resilience. The study highlights the need for targeted policy interventions that prioritize improvements in human resource quality alongside macroeconomic stability. Future research may explore additional socio-economic indicators or extend the analysis to a broader regional scope for comparative insights. Overall, the findings provide empirical support for formulating inclusive development strategies aimed at achieving sustainable economic growth in Bengkulu and similar regions.